Challenges to early childhood education in rural China: lessons from the Hebei province. Issue 5 (3rd May 2016) - Hu, Bi Ying; Roberts, Sherron Killingsworth; Leng Ieong, Sylvia Sao; Guo, Haiying
Abstract : This research study examined the challenges faced by early childhood education (ECE) in rural China based on a qualitative study of 217 kindergarten classrooms in a large agricultural, rural province. This study utilised onsite teacher surveys, interviews, and observational field notes. This investigation's findings revealed important information in regard to (a) enrollment, class size, and student–teacher ratios; (b) facilities, basic furnishings, and materials; (c) teacher qualifications; and (d) curriculum and pedagogy. Kindergartens in the rural province of Hebei, typical of Chinese provinces with economically disadvantaged students and inadequate ECE funding, were found to be of poor quality across every ECE indicator measured. For the future improvement and well-being of children and their families in rural China, the authors recommend reform policy to increase ECE quality by affiliating quality kindergartens with existing elementary public school structures and to improve teacher quality by advancing teacher benefits, professional status, and professional development opportunities.